TET2 Drives 5hmc Marking of GATA6 and Epigenetically Defines Pancreatic Ductal Adenocarcinoma Transcriptional Subtypes - Eyres, Michael; Lanfredini, Simone; Xu, Haonan; Burns, Adam; Blake, Andrew; Willenbrock, Frances; Goldin, Robert; Hughes, Daniel; Hughes, Sophie; Thapa, Asmita; Vavoulis, Dimitris; Hubert, Aline; et al. (Gastroenterology (New York, N.Y. 1943), 2021)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by advanced disease stage at presentation, aggressive disease biology, and resistance to therapy, resulting in an extremely poor 5-year survival rate of <10%. PDAC is classified into transcriptional subtypes with distinct survival characteristics, although how these arise is not known. Epigenetic deregulation, rather than genetics, has been proposed to underpin progression, but exactly why is unclear and is hindered by the technical limitations of analyzing clinical samples. We performed genome-wide epigenetic mapping of DNA modifications 5-methylcytosine and 5-hydroxymethylcytosine (5hmc) using oxidative bisulfite sequencing from formalin-embedded sections. We identified overlap with transcriptional signatures in formalin-fixed, paraffin-embedded tissue from resected patients, via bioinformatics using iCluster and mutational profiling and confirmed them in vivo. We found that aggressive squamous-like PDAC subtypes result from epigenetic inactivation of loci, including GATA6, which promote differentiated classical pancreatic subtypes. We showed that squamous-like PDAC transcriptional subtypes are associated with greater loss of 5hmc due to reduced expression of the 5-methylcytosine hydroxylase TET2. Furthermore, we found that SMAD4 directly supports TET2 levels in classical pancreatic tumors, and loss of SMAD4 expression was associated with reduced 5hmc, GATA6, and squamous-like tumors. Importantly, enhancing TET2 stability using metformin and vitamin C/ascorbic acid restores 5hmc and GATA6 levels, reverting squamous-like tumor phenotypes and WNT-dependence in vitro and in vivo. We identified epigenetic deregulation of pancreatic differentiation as an underpinning event behind the emergence of transcriptomic subtypes in PDAC. Our data showed that restoring epigenetic control increases biomarkers of classical pancreatic tumors that are associated with improved therapeutic responses and survival.